Through mom's eyes : simple wisdom from mothers who raised extraordinary humans - Jones, Sheinelle, 1978- (G.P. Putnam's Sons, 2026)
"When Sheinelle Jones launched "Through Mom's Eyes," a recurring Today show segment interviewing celebrities' mothers about raising successful kids, she had an ulterior motive--she wanted to bring all their wisdom to bear on raising her own three children. So she asked Lin-Manuel Miranda's mom about staying present with kids while working multiple demanding jobs, talked with Lady Gaga's mom about how to recognize bullying, and got tips from Steph Curry's mom on making sure even future NBA royalty does the dishes. She has since interviewed dozens of remarkable women, and then taken their advice home and tried it out on her own family. The result: an extraordinarily candid, warm, and insightful collection of wisdom that has taught Sheinelle valuable lessons about life, love, and parenthood. Now in her first book, Through Mom's Eyes, Sheinelle is ready to share even more of those life-changing secrets (along with her own experiences and stories) with the world. By combining behind-the-scenes insights from top celebrity mothers-such as the moms of Matthew McConaughey, Serena and Venus Williams, and Padma Lakshmi-with her own tales from the trenches of modern parenting, Sheinelle reveals how to make it through the hard parts of motherhood and still tap into the joys of it with empathy, generosity, and solidarity. Part parenting guide, part insight into the rich and famous, and all heart, Through Mom's Eyes is a beautiful celebration of those who are the guiding light for their loved ones--mothers"--